The Effects of Working Memory Updating Training in Parkinson’s Disease: A Feasibility and Single-Subject Study on Cognition, Movement and Functional Brain Response - Walton, Lois; Domellöf, Magdalena Eriksson; Boraxbekk, Carl-Johan; Domellöf, Erik; Rönnqvist, Louise; Bäckström, David; Forsgren, Lars; Stigsdotter Neely, Anna (Frontiers in Psychology, 2021)
In Parkinson’s Disease (PD), the fronto-striatal network is involved in motor and cognitive symptoms. Working memory (WM) updating training engages this network in healthy populations, as observed by improved cognitive performance and increased striatal BOLD signal. This two-part study aimed to assess the feasibility of WM updating training in PD and measure change in cognition, movement and functional brain response in one individual with PD after WM updating training. A feasibility and single-subject (FL) study were performed in which patients with PD completed computerized WM updating training. The outcome measures were the pre-post changes in criterion and transfer cognitive tests; cognitive complaints; psychological health; movement kinematics; and task-related BOLD signal. Participants in the feasibility study showed improvements on the criterion tests at post-test. FL displayed the largest improvements on the criterion tests and smaller improvements on transfer tests. Furthermore, FL reported improved cognitive performance in everyday life. A shorter onset latency and smoother upper-limb goal-directed movements were measured at post-test, as well as increased activation within the striatum and decreased activation throughout the fronto-parietal WM network. This two-part study demonstrated that WM updating training is feasible to complete for PD patients and that change occurred in FL at post-test in the domains of cognition, movement and functional brain response.